2016
DOI: 10.1186/s40201-016-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DRASTIC method by artificial neural network, nitrate vulnerability index, and composite DRASTIC models to assess groundwater vulnerability for unconfined aquifer of Shiraz Plain, Iran

Abstract: BackgroundExtensive human activities and unplanned land uses have put groundwater resources of Shiraz plain at a high risk of nitrate pollution, causing several environmental and human health issues. To address these issues, water resources managers utilize groundwater vulnerability assessment and determination of protection. This study aimed to prepare the vulnerability maps of Shiraz aquifer by using Composite DRASTIC index, Nitrate Vulnerability index, and artificial neural network and also to compare their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Agricultural runoff and industrial wastewater arrives into the river at the south eastern part of Shiraz. The geological information showed that the development that takes place in the area are from old to new such as Formation of Tarbor takes place during Campanian to Maastrichtian, Pabdeh-Gurpi developments occurred in Paleocene, formation of Sachun takes place in Paleocene, Jahrom formation occurred in Eocene, Asmari establishments takes place in Oligocene, Razak formation during Miocene, Agha Jari development occurred in Miocene to Pliocene, formation of Bakhtyari made in Pliocene to Pleistocen, and quarternary alluvial deposits [21].…”
Section: Hydrological Settings and Aquifer Formationmentioning
confidence: 99%
“…Agricultural runoff and industrial wastewater arrives into the river at the south eastern part of Shiraz. The geological information showed that the development that takes place in the area are from old to new such as Formation of Tarbor takes place during Campanian to Maastrichtian, Pabdeh-Gurpi developments occurred in Paleocene, formation of Sachun takes place in Paleocene, Jahrom formation occurred in Eocene, Asmari establishments takes place in Oligocene, Razak formation during Miocene, Agha Jari development occurred in Miocene to Pliocene, formation of Bakhtyari made in Pliocene to Pleistocen, and quarternary alluvial deposits [21].…”
Section: Hydrological Settings and Aquifer Formationmentioning
confidence: 99%
“…CC BY 4.0 License. (Raju et al, 2014), and DRASTIC (Neshat et al, 2014;Baghapour et al, 2014;Baghapour et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted using DRASTIC index to estimate the groundwater vulnerability in the world different regions (Jaseela et al, 2016;Zghibi et al, 2016;Kardan Moghaddam et al, 2017;Kumar et al, 2016;Neshat and Pradhan, 2017;Souleymane and Tang, 2017;Ghosh and Kanchan, 2016;Saida et al, 2017), however, fewer studies have used the CDRASTIC index for evaluation of the groundwater vulnerability (Baghapour et al, 2016;Baghapour et al, 2014;Secunda et al, 1998;Jayasekera et al, 2011;Shirazi et al, 2012;Jayasekera et al, 2008). Boughriba et al (2010) utilized DRASTIC index in geographical information system environment for an estimate of the vulnerability in the aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Given the consequences, a comprehensive risk analysis of groundwater that can provide reasonable and reliable plans for groundwater exploitation and minimize the risk of exploitation and utilization is necessary [12,13]. At present, there are many methods of groundwater risk assessment, such as fuzzy evaluation [14,15], factor analysis [16], neural network analysis [17][18][19], analytic hierarchy process [20][21][22][23] and so on. Zhang et al proposed an approach with analysis hierarchy process and fuzzy comprehensive evaluation integrated together to establish a corresponding index system of groundwater risk assessment [15].…”
Section: Introductionmentioning
confidence: 99%